PEMBERDAYAAN KADER DAN KELUARGA DALAM OPTIMALISASI DETEKSI DINI DAN PENCEGAHAN RISIKO IBU HAMIL DI KELURAHAN PEMURUS DALAM KOTA BANJARMASIN - Tunggal, Tri; Hipni, Rubiati; Sofia, Norlaila; Aprilea, Noor Adha; Noor Adha (Jurnal Bakti untuk Negeri, 2025)
Background: Pemurus Dalam Village in Banjarmasin City is a swampy area witha population of 24,290, including 418 women of reproductive age. Fieldobservations revealed a high prevalence of high-risk pregnancies due to limitedknowledge among families and health cadres regarding early detection ofpregnancy risks. This condition necessitates community empowerment to enhance maternal health literacy and preventive capacities.Objective: This community service aims to enhance the knowledge, awareness, and skills of healthcare professionals and families in identifying early pregnancy risks, while fostering collaboration with healthcare providers.Method: The activity employedparticipatory training and education through a community empowermentapproach. Evaluation was conducted using pre- and post-tests among 20 participants (10 cadres and 10 families of pregnant women).Results: There was asignificant improvement in participants' knowledge, from 0% in the good category before training to 85% after the training. Conclusion: The program effectively enhanced the capacity of cadres and families for early detection of pregnancy risks and can serve as a replicable model for other regions.